NON-LINEAR EFFECTS OF AIRFOIL FORCE DATA ON DESIGN PERFORMANCE OF A LOW-REYNOLDS NUMBER PROPELLER - Reuben, Umunna J; Hiraki, Koju; Shohei, Miyamoto (International Journal of Research -GRANTHAALAYAH, 2018)
Over the last three decades and a half, there has been huge effort to develop high performance propellers suitable for flight in the rarefied Mars atmosphere. This paper describes work undertaken in validating vortex theory in the design of a 2-bladed heavily loaded propeller with a solidity of ≈0.25 and chord based Reynolds number of ≈60k (calculated at 75% radius) at design point. The design was based on minimum induced propeller losses and lifting line theory. 2D-airfoil experiment data of SD7037 collected at Reynolds number of 60k was used for the entire blade design. At design advance ratio, more than 50% of the entire blade radius operated between 40k – 60k Reynolds numbers. A design goal of the propeller was to minimize variation in Reynolds number from hub to tip radius. Wind tunnel tests carried out at Kyushu Institute of Technology were performed in two (2) ways: constant angular velocity and changing airflow velocity over the propeller, and constant airflow velocity and changing propeller angular velocity. The fabricated propeller showed good agreement in efficiency for both test cases. However, considerable discrepancy was observed between theory and experiment in thrust and power. Investigation showed that non-linearity associated with airfoil aerodynamic data not captured by linearization result in a less representative modeling of the airfoil force coefficient and consequently, discrepancy in propeller performance between theory and experiment.